Fracture of porcelain-veneered gold-alloy and zirconia molar crowns using a modified test set-up - Christel Larsson; Marko Drazic; Eddie Nilsson; Per Vult von Steyern (Taylor & Francis Group, 2015)
Objective: The main aim of this study was to compare fracture load and fracture mode of yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) and metal-ceramic (MC) molar crowns using a modified test set-up to produce fractures similar to those seen in vivo, i.e. fractures of the veneering material rather than complete fractures. Materials and methods: 13 high-noble-alloy MC and 13 Y-TZP molar crowns veneered with porcelain were manufactured. The crowns were artificially aged before final load to fracture. Load was applied using a 7 mm diameter steel ball exerting force on the cusps with stresses directed toward the core-veneer interface. Fracture surface analysis was performed using light- and scanning electron microscopy. Results: The test design produced fractures of the veneering material rather than complete fractures. MC crowns withstood significantly (p > 0.001) higher loads (mean 2155 N) than Y-TZP (mean 1505 N) crowns, yet both endure loads sufficient for predictable clinical use. Fracture mode differed between MC and Y-TZP. MC crowns exhibited fractures involving the core-veneer interface but without core exposure. One Y-TZP crown suffered a complete fracture, all others except one displayed fractures of the veneering material involving the core-veneer interface with core exposure. Conclusions: The test set-up produces fractures similar to those found in vivo and may be useful to evaluate the core-veneer interface of different material systems, both metals and ceramics. The study confirms suggestions from previous studies of a weaker core-veneer bond for Y-TZP compared to MC crowns.